Community pharmacy and public health in Great Britain, 1936 to 2006: how a phoenix rose from the ashes. Issue 10 (14th September 2007) - Anderson, Stuart
Abstract : The pharmacy profession in Great Britain has identified public health as a key area for future development; at the same time the government has been keen to make full use of pharmacists in pursuing its public health goals. To date, pharmacy has focused on microlevel activities such as health promotion, medicines management and prescribing advice, rather than on wider public health issues such as health inequalities. The role in health promotion has its origins in the traditional advisory role of the pharmacist, which largely died out following the establishment of the National Health Service in 1948, and was resurrected only following ministerial intervention in 1981. This article traces the origins of the pharmacist's role in public health, illustrating both shifting definitions of public health and changes in pharmacy practice. It describes how the profession was able to re-establish its advisory role and to develop it into a wider contribution to public health, indicating that this process came about as a result of convergence between a professional imperative to develop its role, on the one hand, and state recognition of the need to draw a broader range of health professionals and lay people into public health activities, on the other. Convergence required the securing of government support, confirmed in policy documents; the recognition by pharmacy's professional body that embracing public health is a desirable activity; incentives for community pharmacists to carry out such activities; and support from the wider public health community. This article describes how each of these was achieved.